Evaluation of Brain Death in Laying Hens During On-Farm Killing by Cervical Dislocation Methods or Pentobarbital Sodium Injection - Hernandez, Elein; James, Fiona; Torrey, Stephanie; Widowski, Tina; Schwean-Lardner, Karen; Monteith, Gabrielle; Turner, Patricia V. (Frontiers in Veterinary Science, 2019)
This study investigated changes in the electroencephalograph (EEG) power spectrum as well as physiological and behavioral responses to on-farm killing via mechanical cervical dislocation (MCD), manual cervical dislocation (CD) or intravenous pentobarbital sodium administration in lightly anesthetized laying hens, to evaluate the welfare impact of each method. A mixed group of 44 white Leghorn and Smoky Joe laying hens (60 weeks-old) were anesthetized with isoflurane in oxygen and maintained at 1.5-2% isoflurane/O2 until the killing method was applied. Birds were randomly assigned to one of three experimental groups on each trial day. The EEG was recorded bilaterally in a four-electrode montage. After recording a five-minute baseline, the killing method was applied and EEGs and other behavioral and physiological responses, including convulsions, gasping, cessation of body movements and feather erection were recorded for five minutes. Changes in EEG frequency bands (alpha, beta, delta, theta), median frequency (F50), 95% spectral edge frequency (F95), and total power (Ptot) were used to assess the quality of the on-farm killing event. Within 15s after administration of pentobarbital sodium, there were significant decreases in mean frequency bands, increases in mean F50 and F95, and decreases in Ptot, suggesting brain death. In addition, birds presented a shorter latency to cessation of movement after pentobarbital sodium injection compared to MCD and CD (22s vs. 115s and 136s, respectively). There were significant increases in F95 and decreases in Ptot at 120s after application of CD; and a concomitant decrease in the frequency bands at 135s and isoelectric EEG at 171±15s. Changes consistent with brain death after MCD included isoelectric EEG at 207±23s and a significant decreases in some frequency bands at 300s post application. No other significant spectrum frequency changes were observed in the MCD group, suggesting brain death likely occurred near the 5-minute endpoint. There was no clear association between behavioral, physiological, and EEG responses within CD and MCD treatments. The data demonstrate that pentobarbital sodium induced a rapid death with minimal behavioral and physiological responses regardless of strain of hens. In comparison, use of CD and MCD resulted in a slow onset of brain death in hens.